(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
The overall analysis of marketing of agricultural inputsin Haryana in respect of cotton seeds, wheat seeds, fertilizers, pesticides,and tractors with regards to awareness level of the farmers, usage ofvarieties, features or factors considered for selecting a particular variety,mode of payment, their sources of information, perception regarding the price,product assortment offered by different companies, the influence of retailers,co-farmers and relatives, preference of electronic media and awareness ofrights of the farmers etc. The mode of sale of each source is found differentfrom place to place according to the demands of the farmers. The agency holders/shopkeepers/retailersalways try to influence the farmers for selling the above agricultural inputsprovided by the marketers. In order to satisfy the farmers, every company is tryingto implement marketing mix. The agriculture departments at centre level as wellas state level, Indian Council of Agricultural Research and agriculturaluniversities are likely to witness a sea change in the realm of changingliberalized current scenario. In thisregard the research is carried out and a deep and careful analysis is made.